Analysing Gender Dynamics of the Carbon Credit Aggregator Business Model: A Case Study of Indore Smart City's Sustainable Carbon Trading Practices - Akre, Apurva; Mehrotra, Surabhi; Krishna, Ankita (Calibrating Urban Livability in the Global South, 2024)
This research study delves into the intricate nexus of waste management, carbon trading mechanisms, climate-resilient urban design, and gender dynamics within Indore City’s carbon credit aggregator model. The Swachh Bharat mission has achieved remarkable success in transforming the mindset of Indian citizens and fostering positive behavioural changes. Focused on Swachh Bharat Abhiyan and aligned with the United Nations Sustainable Development Goals (SDGs), the research explores how the city's sustainable carbon trading practices contribute to environmental responsibility. The study emphasizes the impact of the carbon credit aggregator model on climate-resilient practices in reducing carbon emissions. Through a gendered lens, the aim is to explore the unique challenges faced by women in the waste management sector, ensuring an inclusive evaluation of the initiative. The study conducted in Indore City aimed to evaluate women’s contributions to achieving the goals of Swachh Bharat Abhiyan. It assessed their awareness levels and proposed policies promoting women’s leadership and involvement in decision-making. To gauge the potential of the model, the study further analyses the model through environmental, social, economic, and governance viewpoints. This analysis further paves the way for replicating this model in other municipal corporations, fostering sustainable development at the urban level.